The effect of bariatric surgery on inflammatory markers in women with polycystic ovarian syndrome. Issue 6 (November 2018) - Abiad, Firass; Khalife, Dalia; Safadi, Bassem; Alami, Ramzi; Awwad, Johnny; Khalifeh, Fatin; Ghazeeri, Ghina
Abstract: Aim: The aims of this study is to address the improvement in CRP and adiponectin in obese PCOS and non PCOS after bariatric surgery, and to show that obese PCOS women have a slower rate of improvement when compared to obese non PCOS women. Methods: This is a prospective case-control study evaluating the effect of weight loss by sleeve gastrectomy among obese PCOS patients. Results: There was a 36.28% of weight loss among obese PCOS and 33.04% among the control group at 12 months. Both groups showed a significant increase in the adiponectin levels at 3, 6 and 12 months' post-surgery. The rate of increase was higher in the obese non PCOS women (4.93 ± 1.79–9.79 ± 3.9) compared to obese PCOS women (5.05 ± 1.98–7.25 ± 0.21). The CRP levels decreased with weight loss after the surgery to reach statistical significance at 3 months in obese PCOS group (4.18 ± 3.94, p = 0.048). Conclusion: The degree of weight loss after surgery was effective in lowering CRP and increasing adiponectin levels in PCOS women. However, this improvement was slower compared to obese non PCOS patients. A genetic predisposition to insulin resistance might explain these findings.